Coping Strategy during Farm Distress: a Case Study of Cattle Breed Improvement Program in Andhra Pradesh - Anand Reddy, K; Kanaka Durga, P. (Journal of Agricultural Extension Management, 2018)
The income of the farmers can be improved if other enterprises are taken up by the farmer along with crop husbandry in an integrated manner, as they provide supplementary income to the farmers. This article aims to showcase the importance of the dairy enterprise, through breed improvement interventions, in increasing the farmers’ income by taking a case study of the Cattle Breed Improvement Program of JK Trust. An evaluation of the Cattle Breed Improvement Program (CBIP) was carried out with the help of primary data collected from 240 farmer beneficiaries from 20 villages in four districts. It was observed that the program created awareness among farmers towards the benefits of an improved breed over non-descript cattle. The availability of doorstep services could be seen as a model initiative carried out by J.K. Trust. Increase in employment in terms of man days and increased income of the farmers due to breed improvement interventions are noteworthy. The study suggests that in the event of crop failure, the income of the farmers could be protected by other enterprises such as dairy and more so with the breed improvement interventions. There is an urgent need to spread the National Project for Cattle and Buffalo Breeding (NPCBB )breed improvement program in areas which are not covered to address the farm distress.